Management of dystocia due to Schistosomus Reflexus - a case report - Rajoria, Jitendra Singh; Ningwal, Deepak; Singh, A P; Tomar, Priyanshu; Prashant,; Tandia, Neelam (Animal Reproduction Update, 2023)
Schistosomare flexus are a major congenital anomaly which occurs during  embryonic development. Schistosomare flexus are characterized by incomplete  fusion of abdominal wall leading to exposed viscera and marked ventral curvature  of spine. A genetic or chromosomal abnormality, mutation, chromosomal  anomaly, infectious agent, or a combination of these factors may be the cause,  although its etiology is unknown. A Holstein Friesian (HF) cross-bred cow of 4  years with straining and fetal intestine hanging through the vulva was presented  to the veterinary clinical complex for parturition failure. Thus, it was diagnosed  as a case of Schistosomare flexus. With per vaginal examination it was further  confirmed that visceral organs were from the fetus. Therefore, it was decided to  remove the fetus through caesarean section.
Keywords: Schistosomusre flexus; Dystocia; Monster